Lee Silverman voice treatment versus NHS speech and language therapy versus control for dysarthria in people with Parkinson’s disease (PD COMM): pragmatic, UK based, multicentre, three arm, parallel group, unblinded, randomised controlled trial - Catherine Sackley; Caroline Rick; Marian Brady; Rebecca Woolley; Christopher R Burton; Smitaa Patel; Patricia Masterson‐Algar; Avril Nicoll; Christina H. Smith; Sue Jowett; Natalie Ives; Gillian Beaton; et al. (2024)
To assess the clinical effectiveness of two speech and language therapy approaches versus no speech and language therapy for dysarthria in people with Parkinson's disease.